Anthropogenic contaminants in glacial environments I: Inputs and accumulation. (August 2022) - Beard, Dylan B; Clason, Caroline C; Rangecroft, Sally; Poniecka, Ewa; Ward, Kim J; Blake, Will H
Historically, glaciers have been seen as pristine environments. However, recent research has shown that glaciers can accumulate and store contaminants over long timescales, through processes such as atmospheric deposition, sedimentation, glacial hydrology and mass movements. Studies have identified numerous anthropogenically derived contaminants within the global cryosphere, including the six we focus on here: fallout radionuclides; microplastics; persistent organic pollutants; potentially toxic elements; black carbon and nitrate-based contaminants. These contaminants are relatively well-studied in other environments; however, their dynamics and role in glaciated systems is still poorly understood. Therefore, it is important to assess and quantify contaminant levels within the cryosphere, so that current and future threats can be fully understood and mitigated. In this first progress report ( Part I: Inputs and accumulation ), we review the current state of knowledge of six of the most common anthropogenic contaminants found in the cryosphere, and consider their sources, transportation, accumulation and concentration within glacial systems. A second progress report ( Part II: Release and downstream consequences ) will outline how these contaminants leave glacial systems and the consequences that this release can have for communities and ecosystems reliant on glacial meltwater.